Randomized control trial to compare the effectiveness of mifepristone followed by misoprostol at 12 hours interval versus misoprostol alone in second trimester medical termination of pregnancy - Bedi, Preet Kamal; Saini, Arunima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Mifepristone priming in second trimester abortions not only decreases the induction-abortion interval (IAI) but also lessens the total misoprostol dose required and hence reduces adverse effects. The present study aims to compare the role of mifepristone priming 12 hours before misoprostol administration so as to increase patient compliance and shorten the duration of hospital stay. Methods: This prospective study was conducted over a period of one year, on 50 patients requiring second trimester abortion, at Department of Obstetrics and Gynaecology, Government Medical College, Amritsar. The patients were divided into two groups with 1:1 randomization. In Group A, 25 women were given tablet mifepristone 200 mg orally followed 12 hours later by tablet misoprostol 400 µg per vaginum followed by the same dose 3 hourly for a maximum of five doses per 24 hours. In group B, 25 women received only tablet misoprostol 400 µg vaginally in the posterior fornix followed by the same dose 3 hourly for a maximum of five doses per 24 hours. Primary outcome was to compare the completeness of expulsion of products of conception by pelvic ultrasound after 48 hours of the last dose administered. Secondary outcome was to compare the Induction abortion interval (IAI), mean dose of misoprostol required, side effects, effect of parity, gestational age and cervical dilatation on IAI with both the regimens used. Results: The success rate was 76% in group A and 64% in group B. The mean induction abortion interval in group A was 8.9±4.70 hours whereas in group B, it was 13.14±6.03 hours and this difference was statistically significant (p = 0.008). A statistically significant difference was also observed in mean dose of misoprostol required in group A and B being 1232.00±398.60 µg and 1584.00±423.94 µg respectively (p=0.004). The side effects were less in group A. Parity and cervical dilatation hold an inverse relation with the mean IAI whereas it has a direct relation with the gestational age. Conclusions: Regimen involving mifepristone priming 12 hours before misoprostol is better than misoprostol alone regimen with significant reduction in IAI, mean dose of misoprostol and less side effects.